Daya Juang Akademik Mahasiswa dalam Mengikuti Pembelajaran Offline Pasca Online - Gafar, Bona; Barus, Gendon (Jurnal Bimbingan dan Konseling Terapan, 2023)
The purpose of this study: (1) Describing the level of academic fighting power of students in participating in offline post online learning. (2) Identifying academic fighting power measurement items whose scores are low or not optimal in students of the Guidance and Counseling study program at Sanata Dharma University Class of 2020, who take part in offline post-online learning. The research method used is descriptive quantitative research method, by distributing questionnaires online to Guidance and Counseling students of Sanata Dhrama University class of 2020. By analyzing the level of fighting power of these students, it is hoped that it will be an input for lecturers to see obstacles and difficulties in dealing with learning during the online to offline transition. From the results of the research conducted, it shows that 2020 Sanata Dharma University Guidance and Counseling students have a high level of fighting power in participating in learning during the online to offline transition, this can be seen from the results of the categorization test of the level of fighting power which shows 64% of students have a high level of fighting power in participating in learning during the online to offline transition.